Saving the Greater Adjutant Stork by Changing Perceptions and Linking to Assamese Traditions in India - Barman, Purnima Devi; Sharma, D. K.; Cockrem, John F.; Malakar, Mamani; Kakati, Bibekananda; Melvin, Tracy (Ethnobiology Letters, 2020)
The Greater Adjutant Stork (Leptoptilos dubius), locally known as Hargila (the bone swallower) is an endangered bird with an estimated global population of less than 1200. Habitat loss, poisoning, and poaching have caused large declines in populations of this stork in South Asia, with the Brahmaputra valley in Assam in northeastern India now the last stronghold for the species. The stork nests colonially in privately owned trees within thickly populated villages. Tree owners would cut down trees to prevent rotten food and excreta of this carnivorous bird from falling into their backyards. A change in attitudes of the nest-tree owners towards keeping their trees and towards Greater Adjutants has been the key to stork conservation. A conservation project involving community development, education and outreach, interlinking storks with local traditions and cultures, and capacity building of local communities was initiated in 2007. A rural women’s conservation group named the Hargila Army was instituted and strong feelings of pride and ownership for the storks by the villagers have been generated. Cash incentives for nest protection were deliberately avoided, with schemes that indirectly contribute to the livelihoods of nest-tree owners and other villagers introduced instead. The success of the conservation program is shown by the increase in the number of nesting colonies in the village area of Dadara, Pachariya, and Singimari in Kamrup District in Assam from 28 nests in 2007–08 to 208 nests in the 2019–20 breeding season, making this the largest breeding colony of Greater Adjutant Storks in the world.